Predictors and Moderators of Panic Disorder: Cognitive Behavioral Therapy vs. Acceptance and Commitment Therapy - León-Quismondo, Leticia; Lahera, Guillermo; Fernández-Liria, Alberto; López-Ríos, Francisca; Saiz-Ruiz, Jerónimo; Ibáñez, Ángela; García-Montes, José M.; Stiles, Bryan J. (Psicothema, 2025)
Background: Understanding variables that influence therapy outcomes can improve the results of interventions and reduce socio-health costs. The current study examined possible predictors and moderators of outcome (age, gender, duration of panic disorder, motivation to change, conscientiousness, and experiential avoidance) in Cognitive Behavioral Therapy (CBT) and Acceptance and Commitment Therapy (ACT). Method: Eighty participants with a diagnosis of panic disorder, 56 women and 24 men, with an average age of 38 years, received 12 group sessions of CBT or ACT. They were assessed with several measures at pre-treatment, post-treatment, and 3-month follow-up. Results: CBT outperformed ACT among older subjects, men, and those with a shorter duration of panic disorder. ACT outperformed CBT among younger subjects, women, and those with a long duration of panic disorder. In general, the greatest improvements in both CBT and ACT were in older subjects, women, those with a long duration of panic disorder, those in the contemplation stage, and those with high experiential avoidance. Conclusions: Although future studies are necessary, there appear to be predictors and moderators of the effectiveness of CBT and ACT. Taking these variables into account can help improve treatment for people with panic disorder.